Psicología positiva: algunas aplicaciones a la educación - Rodríguez de Los Ríos, Luis (2017)
Positive psychology, considered as a new vision within psychology, arises with the expectation of knowing the characteristics, processes, and conditions of the optimal functioning of people. This is used to promote a full and meaningful life from the individual perspective to the social projection. This article provides a theoretical-practical analysis of the concepts and applications related to the positive psychology approach; which is addressed from the field of education by promoting a teaching-learning process from and to happiness. Establishing an educational path from and to happiness would imply on the part of the educators a personal commitment to know themselves, to have values, and to pursue goals. The current importance of positive psychology within education leads to the need to work on this topic in order to give it the importance it deserves and show the beneficial effects it has on both teachers and students in an educational environment. Therefore, we must know the tools that it provides to be able to apply them in the classroom. Through the educational proposals, the happiness of the students can become a goal to reach in the day to day, making the learning and the stage of schooling, a period, in which we enjoy and also learn to be happy in the here and now without neglecting the importance of the past and the future.